Social Forestry : Application of Remote Sensing Technique - Pant, D. N. (Indian Forester, 1993)
The Social Forestry schemes are mostly executed under microlevel planning of pockets of wastelands within and around the villages, road, canal and railway lines sides. Remote sensing techniques are effective and useful in evaluation of the land suitable for plantation and selection of species.